A Novel Herbal Formula Induces Cell Cycle Arrest and Apoptosis in Association With Suppressing the PI3K/AKT Pathway in Human Lung Cancer A549 Cells. (March 2014) - Xiong, Fei; Jiang, Miao; Huang, Zhenzhou; Chen, Meijuan; Chen, Kejun; Zhou, Jing; Yin, Lian; Tang, Yuping; Wang, Mingyan; Ye, Lihong; Zhan, Zhen; Duan, Jinao; et al.
Aim of the study . In recent years, the incidence of lung cancer, as well as the mortality rate from this disease, has increased. Moreover, because of acquired drug resistance and adverse side effects, the effectiveness of current therapeutics used for the treatment of lung cancer has decreased significantly. Chinese medicine has been shown to have significant antitumor effects and is increasingly being used for the treatment of cancer. However, as the mechanisms of action for many Chinese medicines are undefined, the application of Chinese medicine for the treatment of cancer is limited. The formula tested has been used clinically by the China National Traditional Chinese Medicine Master, Professor Zhonging Zhou for treatment of cancer. In this article, we examine the efficacy of Ke formula in the treatment of non–small cell lung cancer and elucidate its mechanism of action. Methods . A Balb/c nude mouse xenograft model using A549 cells was previously established. The mice were randomly divided into normal, mock, Ke, cisplatin (DDP), and co-formulated (Ke + DDP) groups. After 15 days of drug administration, the animals were sacrificed, body weight and tumor volume were recorded, and the tumor-inhibiting rate was calculated. A cancer pathway finder polymerase chain reaction array was used to monitor the expression of 88 genes in tumor tissue samples. The potential antiproliferation mechanism was also investigated by Western blot analysis. Results . Ke formula minimized chemotherapy-related weight loss in tumor-bearing mice without exhibiting distinct toxicity. Ke formula also inhibited tumor growth, which was associated with the downregulation of genes in the PI3K/AKT, MAPK, and WNT/β-catenin pathways. The results from Western blot analyses further indicated that Ke blocked the cell cycle progression at the G1/S phase and induced apoptosis mainly via the PI3K/AKT pathway. Conclusion . Ke formula inhibits tumor growth in an A549 xenograft mouse model with no obvious side effects. Moreover, Ke exhibits synergistic antitumor effects when combined with DDP. The mechanism of action of Ke is to induce cell cycle arrest and apoptosis by suppressing the PI3K/AKT pathway. Further research will be required to determine the mechanism of action behind the synergistic effect of Ke and DDP.